Implementing Collaborative Governance in Investment for Regional Development in Southwest Papua - Widjasenaa, Herryanus FR; Ahmad, Badu; Yunus, Muhammad (KnE Social Sciences, 2025)
This article examines the application of a collaborative governance approach in regional investment management, emphasizing the importance of multiactor involvement across sectors. Sorong City, as the gateway to the Southwest Papua region, has a strategic position to become a pilot project for a collaborative investment governance model that is participatory and adaptive to the local context. The perspective of investment policy management is closely related to governance, where the process and systematics of investment services begin with the government process, which then develops into investment opportunities and realities in the region. This article aims to critically examine theoretically the various potential applications of a collaborative governance approach in investment governance in Sorong City, as well as to formulate policy strategies that can encourage the creation of inclusive, transparent, and sustainable investment. The research technique used is a qualitative approach by searching for relevant literature and a number of secondary data sources through reports of various study results that focus on the involvement of collaborative governance in investment services. The formation of data sourced from literature and secondary data is then analyzed using an argumentative approach to explain the application of collaborative governance that has the potential to increase transparency, effectiveness, and sustainability of investment in the West Papua Province. The results of the study indicate that the process of applying the principle of collaborative governance in increasing investment to encourage regional development in the West Papua region, especially Sorong City, has various structural and cultural challenges. From the perspective of regional government bureaucracy, the social structure of crocodiles greatly determines the application of the collaborative governance approach in increasing investment potential through communication channels between actor and agency networks and expanding access with the concept of coaching. In addition, the development of investment programs in the context of Sorong City regional development planning should be an inseparable part, so that internal strength becomes an effective locomotive in the framework of encouraging investment access. A number of obstacles were found conceptually and through analysis of data reports from various sources found both internally and externally.